Transgression in Lyudmila Ulitskaya’s novel Jacob’s Ladder - Szabó, Tünde (Literatūra, 2019)
The status of the boundary that separates and connects the different spheres of existence and the possibility of crossing this boundary (transgression) are the subject of many studies in different fields of the humanities. Transgression is also closely linked to the question of the relationship between reality and fiction; consequently, it can be considered as one of the fundamental problems of literary theory. It is exactly the incompleteness and theoretical openness of the literary work and the permeability of reality and fiction that the motto of L. Ulitskaya’s novel Jacob’s Ladder takes as its theme, thus directing the reader’s attention to the acts of crossing boundaries in the work. In this paper, I examine the various sources of transgression; on the one hand, in the course of the heroine’s life, and on the other hand, in relation to the different semiotic systems that open up within the plot.